Business economics - Dransfield, Robert, 1952- (Routledge, 2025)
"Business Economics introduces the theory and practice of economics for non-specialist students new to the topic. Business Economics, Second Edition, is designed to provide a general introduction to the discipline of Business Economics, covering an important part of first year studies and beyond. The new edition retains the successful structure of the previous edition but, like any good business economics text, includes new and updated case studies and examples to reflect present-day economic global realities. Suitable for introductory-level students who are seeking a comprehensive but accessible way into the subject, Business Economics, Second Edition, is bolstered by a host of activities, review questions and further reading, making it the ideal choice for undergraduate students and lecturers"-- Provided by publisher.
Keywords: Managerial economics.; elektronické knihy; electronic books